EKSTRAKSI DAN UJI STABILITAS EKSTRAK DAUN TARUM (Indigofera tinctoria) SEBAGAI PEWARNA KAIN TENUN DI DAERAH ENDE NUSA TENGGARA TIMUR - Tima, Maria Tensiana; Rendo, Donatus; Sarah, Mardiah (Jurnal Belantara, 2024)
Since ancient times, woven fabric craftsmen in the Ende area have used tarum leaves as a dye in their woven fabrics. Extraction of color pigments in tarum leaves is carried out by soaking in water or seawater for a certain length of time so as to produce quality color pigments.This study aims to determine the stability of natural dyes in tarum leaves which are used as dyes for woven fabrics in the Ende area of ​​East Nusa Tenggara which were extracted using water and seawater as solvents. The research was carried out in the laboratory of the Faculty of Agriculture, University of Flores using the experimental method. The results showed that tarum leaves produced the optimum wavelength when soaked for 24 hours and there was a decrease in the color stability of the tarum leaf extract due to storage factors, increased temperature, duration of sunlight and increased concentrations of oxidizing agents.